SEBAB-SEBAB KESALAHAN DALAM TAFSIR - abdul Halim (SYAHADAH : Jurnal Ilmu al-Qur'an dan Keislaman, 2014)
In some works of quranic interpretation, it was found so many mistakes in understanding the Qur’an. This paper tries to describe the cause of mistakes in interpreting the Quran which has been initiated by some Quranic thinkers in their works. Some causes of misunderstanding in interpreting al-Qur’an sometimes come from the interpreter its self like carelesness, uncomprehensive understanding of arabic language, ideological and political interest and another causes. In the other hand, it come from outside of the interpreter such as unvalid sources and the pressure of authoritarian government where the interpereter live. After expalaining the causes of misunderstanding in interpretation, the writer tries to analise it and strive to draw its implication for the possibility of quranic interpretation.